Strategi Guru dalam Menanamkan Nilai Disiplin dan Tanggung Jawab Anak Usia Dini melalui Pembelajaran Berbasis Karakter di Era Digital di RA Aisyiyah Bolang Kabupaten Enrekang - Miftahul Jannah; Yunus Busa; Haerusman; Suparman; Nurwafiqah Amirah Budi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to describe teachers' strategies in instilling the values of discipline and responsibility in early childhood through character-based learning in the digital era at RA Aisyiyah Bolang, Enrekang Regency. The study used a descriptive qualitative approach with research subjects consisting of the principal, class teachers, and parents of students. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis used the Miles, Huberman, and Saldaña model which includes data condensation, data presentation, and drawing conclusions. The results of the study indicate that teachers' strategies in instilling the values of discipline are carried out through routine habits, role models, positive reinforcement, and the use of educational digital media. Instilling the values of responsibility is done through giving simple tasks, habits of maintaining the cleanliness and tidiness of the learning environment, and the use of digital media that contain moral messages. Supporting factors include teacher commitment, school support, and parental cooperation, while inhibiting factors include uncontrolled use of gadgets at home, differences in parenting styles, and limited use of technology in learning. This study shows that character-based learning combined with the targeted use of digital media can support the formation of discipline and responsibility in early childhood.